The Management Problems of Patient with Chronic Hepatitis B Infection and Its Reactivation - Tri Asih Imro'ati; Ummi Maimunah (The Indonesian Society for Digestive Endoscopy, 2019)
Hepatitis B virus infection is a major global health problem in the world and particularly in Indonesia. It can cause chronic infection and puts people at high risk of death from cirrhosis and liver cancer. In this case, we will show about the problems that may occur while we manage a patient. A 55 years old man with chronic hepatitis B has been treated with Telbivudin 600 mg for 8 years and and then stop for 2 years (The HBsAg has been non reactive, HBeAg has been seroconversion from positive to negative, and HBV DNA has been not detected since 2014 until January 2016). In 2018, patients undergo surgery to remove nodules in the liver. After that, there were transaminase and bilirubin elevation, and then HBsAg become reactive again. After giving combination therapy of Telbivudin 600 mg with Entecavir 0.5 mg and metyl prednisolone 8 mg (per os, three times a day) for 1 months, the transaminase became decrease, but the bilirubine was still high. The patient was reported to have died in February 2019 after being hospitalized in a hospital outside Java, so we could not know or investigasted the cause of his mortality.